Analisis Pelaporan Insiden Keselamatan Pasien di Unit Rawat Inap Siloam Hospitals, Manado, Indonesia - Citra M. N. Lombongkaehe; Erling D. Kaunang; Herman Karamoy (Medical Scope Journal, 2023)
Abstract: Patient safety is now a top priority for hospitals. This study aimed to analyze patient safety incident reporting at inpatient unit of  Siloam Hospitals Manado. This was a qualitative study using eight informants. The results showed that patient safety incident reporting at the hospital inpatient unit was carried out using the Q-Pulse application. The incident register on the incident report form in the Q-Pulse application was a maximum of 24 hours after the incident occurred or the risk was known. The inhibiting factors or obstacles in patient safety incident reporting was the slow performance of accessing the Q-Pulse application, the busyness of staff or employees with their main duties, and employees who were still afraid to report due to be blamed. Efforts to overcome obstacles in patient safety incident reporting were inter alia refreshing the internet network, adding signal boosters or wifi boosters which will be coordinated with the Siloam Head Office. In addition, Siloam Hospitals Mando planned to migrate from the Q-Pulse application where the function was still the same but used a different platform, namely the website-based Medblaze. In conclusion, patient safety incident reporting at the Siloam Hospitals Manado inpatient unit was carried out using the Q-Pulse application with a maximum of 24 hours after the incident occurred or the risk was known. There were varied inhibiting factors or obstacles in the patient safety incident reporting and several efforts had been done to overcome them. Keywords: patient safety; safety incidents; incident reporting   Abstrak: Keselamatan pasien kini menjadi prioritas utama bagi rumah sakit. Penelitian ini bertujuan untuk menganalisis pelaporan insiden keselamatan pasien di unit rawat inap Siloam Hospitals Manado. Penelitian ini menggunakan metode kualitatif dengan delapan orang informan. Hasil penelitian mendapatkan bahwa pelaporan insiden keselamatan pasien di unit rawat inap Rumah Sakit menggunakan aplikasi Q-Pulse. Register insiden pada formulir laporan insiden di aplikasi Q-Pulse maksimal 24 jam setelah insiden terjadi atau risiko diketahui. Faktor penghambat atau kendala dalam pelaporan insiden keselamatan pasien di unit rawat inap yaitu performa yang lambat terhadap akses aplikasi Q-Pulse, kesibukan para staf atau karyawan dengan tugas pokoknya dan karyawan yang masih merasa takut melaporkan karena akan disalahkan. Upaya yang dilakukan untuk mengatasi kendala dalam pelaporan insiden keselamatan pasien di unit rawat inap ialah melakukan refreshment jaringan internet, menambah penguat signal atau penguat wifi yang akan dikoordinasikan bersama Siloam Head Office. Simpulan penelitian ini ialah pelaporan insiden keselamatan pasien di unit rawat inap Siloam Hospitals Manado dilakukan menggunakan aplikasi Q-Pulse maksimal 24 jam setelah insiden terjadi atau risiko diketahui. Terdapat beberapa faktor penghambat atau kendala dalam pelaporan insiden keselamatan pasien di unit rawat inap dan telah dilakukan upaya-upaya untuk mengatasinya Kata kunci: keselamatan pasien; insiden keselamatan; pelaporan insiden